Economics and Social issues: How changes in the Economy Affect Society (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The economy plays a vital role in forming our society. Changes which are happening in the economy do not always stay same and determine opportunities and hardships alike. As the value of exports and imports flourish, the income of the country starts to grow from business taxes. Economic changes in business can come from various different factors, citing taxation, inflation, government spending, various changes in GDP or exchange rates. The economy is considered to be a complex and ever-changing system that significantly impacts society and the lives of nation. Economic behavior, market fluctuations and policies of the government play a vital role in developing social and economic landscape. In this article, various ways in which economic factors can have a profound impact on society and individuals will be discussed.